Optimal Dose Determination of Gamma Ray Irradiation of Alocasia suhirmaniana Yuzammi & A. Hay: Optimal Dose Determination of Gamma Ray Irradiation of Alocasia suhirmaniana Yuzammi & A. Hay - Mulyani, Melza; A Husaini, Iin Pertiwi; Hariri, Muhammad Rifqi; Zulkarnaen, Rizmoon (Universitas Negeri Surabaya, 2025)
Alocasia suhirmaniana Yuzammi & A. Hay belongs to the Araceae family and has the potential for ornamental use. Nevertheless, this plant exhibits a limited leaf count and pliable leaf stems, necessitating the application of breeding techniques for its improvement. One important strategy empeloyed to improve the quality of ornamental plants is the breeding, which involves the use of gamma ray irradiation techniques. The objective of this study is to determine the developmental patterns and appropriate dosage levels of LD20 and LD50 Gamma ray irradiation in A. suhirmaniana callus. The development of callus, the quantity of shoots, and the establishment of rooted explants exhibit a stochastic pattern, with a decrease observed at a dosage of 5 Gy and an increase observed at 10 Gy. The LD20 and LD50 values for Gamma ray irradiation in A. suhirmaniana callus fall within the dose range of 7.14 Gy and 15 Gy, respectively. This dosage range is recommendedto achieve a greater diversity in genotypes and phenotypes. By successfully finding the optimal dosage of gamma ray irradiation, plant selection can be improved through enhancing genotype and phenotype characteristics.